Education on the Use of Masks and Hand Hygiene in Preschool Age Children During the Covid-19 Pandemic At Mentari Kindergarten, West Pilohayanga Village, Telaga District, Gorotalo Regency - Andi Akifa Sudirman; Dewi Modjo; Anshor Ahmad; Ai Cucu Suryani; Ainun N. Allade; Noval Ismail (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Coronaviruses are a large family of viruses that cause disease in humans and animals. In humans, it usually causes respiratory tract infections, ranging from the common cold to serious illnesses such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). This virus spreads very quickly and has spread to almost all countries, including Indonesia, this is certainly very disturbing to all levels of society, preschool age children are one of the age groups that are vulnerable to being infected with COVID-19. This is the goal of community service activities to increase the knowledge of preschool age children with